KEBIJAKAN KEUANGAN NASIONAL TERHADAP PERMASALAHAN EKONOMI DAN BISNIS SELAMA PANDEMI COVID-19 DI INDONESIA - Maria Magdalena Bate’e; Sipur Sipur; Rusmasari Marisya; Almastoni Almastoni; Tri Melda Mei Liana (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Indonesia is a country affected by the Covid-19 outbreak, and this has caused various shocks, including in the economic and business sectors. In this case the economic side offers several solutions and the role of policy for the economy during the face of the co-19 pandemic. The purpose of this study is to determine the impact of the presence of the National Financial Policy on the field of Economy and Business in Indonesia today. The type of research used is a descriptive qualitative approach method with data analysis techniques and library research. The results of this study indicate that the Covid-19 Pandemic has had an impact on the global economy including the economy in Indonesia. This causes a decrease in demand for products and also affects investment realization. In this case the National Financial Policy has an impact and provides solutions in the field of Economy and Business during a pandemic including: (1) direct cash disbursement; (2) the existence of superior business capital assistance for the business sector or MSMEs; (3) increasing economic and financial literacy through the development of financial technology.